Remoção físico-químico do fósforo por floco-sedimentação aplicado ao pós-tratamento de efluente de abatedouro avícola - Menegaz, Rosdaéli Cecconello (2011)
The release of effluents with high organic loads and nutrients for poultry industries of the branch has been causing serious environmental problems. Among the macronutrients, phosphorus, is appointed as the one responsible for the phenomenon of eutrophication of water bodies, causing the imbalance of the aquatic ecosystem and the degeneration of water quality. As a result of environmental problems generated by disposal of waste and inefficiency of treatments to fully remove the phosphorus, it became necessary to study the physical-chemical by-settling floc with different coagulants (ferric chloride, aluminum sulfate, chloride and oxide calcium) at different concentrations as a way to optimize the process for better removal of phosphorus in less time. The concentrations used were 100 mg / L and 300 mg / L of pH and kept in optimal condition for the use of different coagulants. The flocculation time was approximately 10 minutes at a speed of 40 rpm, while the clotting occurred in less time (115 seconds), but its speed remained at 120 rpm. The physical-chemical treatment by-settling floc for post-treatment can be efficient for the removal of phosphorus in effluent from the poultry industry